Dampak Penggunaan Gedget Berlebihan Terhadap Konsentrasi dan Kedisiplinan Siswa dalam Proses Belajar Mengajar - Abdul Latif; Nila Lailatul Fitri; Hilmi Najamuddin; Gina Ilhami Fatin; Sefty Cahyaningtyas; Ewit Nurdayanti; Teti Hifsatun Aini; Muhammat Riyandi; M. Sastra Budiyawan (Alpatih Harapan Semesta, 2026)
This study examines the negative impact of excessive gadget use on students’ concentration and discipline in the teaching and learning process. With the rapid development of digital technology, gadgets have become an inseparable part of students’ daily lives. However, uncontrolled use, particularly for non-educational activities such as social media and online gaming, significantly reduces students’ concentration levels. This is indicated by shortened attention spans, frequent distractions caused by notifications, and decreased ability to comprehend learning materials effectively. In addition, gadget dependency also negatively affects students’ discipline in the school environment, including violations of classroom rules regarding device usage, irresponsible attitudes toward academic tasks, and delays in assignment submission. The combination of these impacts potentially disrupts the effectiveness of the learning process and lowers students’ academic achievement. Therefore, strategic efforts involving schools, teachers, and parents are necessary to establish clear boundaries, provide education on healthy digital time management, and strengthen digital literacy so that students can use gadgets wisely. In this way, technology can function as a supportive learning tool rather than a primary source of distraction in education.